Acute negative effect of the surgical type facemask in the maximal oxygen consumption in healthy subjects - Garza Saucedo, David; Morales Elizondo, Dulce Edith; Morales Corral, Pedro Gualberto; Salinas Torres, Víctor Michael (2021)
BACKGROUND: The maximal oxygen consumption (VO₂Max) may be significantly reduced in presence of the use of surgical type facemask. A possible explanation for this outcome could be due to reduction found in the oxygen saturation (Sat%O₂) at rest. PURPOSE: To determine if the surgical type mask has a negative effect in VO₂Max, as well as any variation in the levels of Sat%O₂. METHODS: Fifteen healthy Mexican subjects were evaluated. The VO₂Max was indirectly measured by the Course Navette (Leger) Test and the Sat%O2 was measured using an oximeter (XIGNAL, model: MD300C2, Beijing Choice Electronic Technology Co., Ltd, China). These variables were tested in different times as follows: at rest without facemask (RWOFM), after the course navette test without facemask (CNWOFM), at rest with facemask (RWFM), and after the course navette with facemask (CNWFM). Descriptive statistical analysis and a contingency table (chi square, Fisher exact test) were performed with SPSS version 22 (IBM, Armonk, NY, USA). A P value <0.05 was considered significant. RESULTS: The mean age was 21.9 ± 2.2 years. The mean VO₂Max without facemask resulted in 34 ± 5.1 ml/Kg/min whereas those with facemask 33.2 ± 5.3 ml/Kg/min (P <0.05). The median Sat%O₂ in RWOFM was 96 ± 2.9%, meanwhile in RWFM was 94 ± 3.8% (P <0.05). The CNWOFM was 96 ± 5.9% and the CNWFM was 93 ±7.0% (P >0.05). CONCLUSION: Surgical facemask may have an acute negative effect in the VO₂Max and in Sat%O₂ at rest, which could impact in daily activities of healthy individuals, particularly, those with cardiorespiratory disorders. Further exploration of these outcomes is required.